2018
DOI: 10.1051/matecconf/201825005003
|View full text |Cite
|
Sign up to set email alerts
|

Failure factors of Makkah’s mega construction projects: qualitative study

Abstract: Makkah city in Saudi Arabia is the holiest place for all Muslims across the world due to the presence of Masjid Al-Haram where the “KAABA” is located. In the holy city of Makkah, mega construction projects are currently under construction to accommodate the increased numbers of pilgrims. These mega projects faced many impediments and challenges to be completed successfully. Hence, this paper presents an investigative study on failure factors of mega Makkah construction projects, particularly from the site mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Adam et al [27] have concluded their literature review for all the publications in delay of mega projects with seven groups and less than 30 factors. Al-Kharashi and Skitmore [25] and Al-Emad and Rahman [26] have almost similar results because they have targeted the same area, which is Saudi Arabia. The authors of [24,29] have concentrated on the management issues as the main reasons of delay in the mega projects.…”
Section: Main Barrier Groupsmentioning
confidence: 79%
See 4 more Smart Citations
“…Adam et al [27] have concluded their literature review for all the publications in delay of mega projects with seven groups and less than 30 factors. Al-Kharashi and Skitmore [25] and Al-Emad and Rahman [26] have almost similar results because they have targeted the same area, which is Saudi Arabia. The authors of [24,29] have concentrated on the management issues as the main reasons of delay in the mega projects.…”
Section: Main Barrier Groupsmentioning
confidence: 79%
“…Al-Emad and Rahman [26] have mentioned 58 failure factors gathered in four groups as the failure factors of Makkah's mega construction projects. These groups are client with 17 factors, contractor with 27 factors, consultant with 10 factors, and external with 4 factors.…”
Section: Main Barrier Groupsmentioning
confidence: 99%
See 3 more Smart Citations